2016
DOI: 10.2320/matertrans.f-m2015841
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Number of Graphite Nodules on Fatigue Limit and Fracture Origins in Heavy Section Spheroidal Graphite Cast Iron

Abstract: The purpose of this study is to investigate the effects of number of graphite nodules on fatigue limit and fracture origins in spheroidal graphite cast iron where carbon content and the number of graphite nodules are changed. As specimens, spheroidal graphite cast irons with 3.0, 3.2, 3.4, 3.6 and 3.8 mass% carbon content were produced respectively. Matrix was conducted pearlite (PDI) and ausferrite (ADI) by heat treatment (normalizing and austempering). The mean diameter of the graphite nodule decreases as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…In order to validate the proposed model, further experimental data were taken from the literature [9][10][11]25,26,28,29,33 where mechanical and fatigue properties (load ratio equal to 0 or −1) of as-cast ferritic ductile cast irons with long solidification times have been investigated. These works reported the actual mechanical properties of the materials and the dimension of the intrinsic initiating defects.…”
Section: Fatigue Resistance Prediction Of As-cast Heavy Section Ducmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to validate the proposed model, further experimental data were taken from the literature [9][10][11]25,26,28,29,33 where mechanical and fatigue properties (load ratio equal to 0 or −1) of as-cast ferritic ductile cast irons with long solidification times have been investigated. These works reported the actual mechanical properties of the materials and the dimension of the intrinsic initiating defects.…”
Section: Fatigue Resistance Prediction Of As-cast Heavy Section Ducmentioning
confidence: 99%
“…In many works found in literature, [8][9][10][11][12] various types of solidification defects have been studied, in order to evaluate their influence on the static and fatigue resistance of the components. The ultimate tensile strength and the elongation at failure are lowered by solidification defects, while hardness and yield stress are less affected.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the sphericity and spatial distribution of nodules affect strength and toughness. Fatigue strength is influenced by count and diameter [10,11].…”
Section: Graphite Morphology and Microstructure Of Roll Core Before Amentioning
confidence: 99%
“…As a phase of the DCI, the graphite must have some changes during this heating process. For this objective, the morphological changes of spheroidal graphite under the continuous heating were observed by HM-350 high temperature metallographic microscope [11]. It illustrates that the transformation of pearlite into austenite after 1023 K has been very obvious.…”
Section: Graphite Morphology Analysis In the Bimetallic Bonding Intermentioning
confidence: 99%
“…For this reason, the requirements of these manufacturers include a volume fraction of pearlite lower than 5%, in addition to a spheroidal morphology in the primary graphite (Lacaze et al, 2016). Recent studies have shown that factors such as graphite morphology and the number of graphite nodules per unit area have a significant effect on the in-service behaviour of the material, especially its fatigue strength (Shiraki et al, 2016).…”
Section: Introductionmentioning
confidence: 99%